Application of nanomaterials in solar thermal energy storage - Shamshirgaran, S.R. (Springer Verlag, 2018)
Solar thermal conversion technology harvests the sunâs energy, rather than fossil fuels, to generate low-cost, low/zero-emission energy in the form of heating, cooling or electrical form for residential, commercial, and industrial sectors. The advent of nanofluids and nanocomposites or phase change materials, is a new field of study which is adapted to enhance the efficiency of solar collectors. The concepts of thermal energy storage technologies are investigated and the role of nanomaterials in energy conversion is discussed. This review revealed that although the exploitation of nanomaterials will boost the performance of solar collectors almost in all cases, this would be accompanied by certain challenges such as production cost, instability, agglomeration and erosion. Earlier studies have dealt with the enhancement of thermal conductivity and heat capacity; however, less attention has been given to the facing challenges. Moreover, no exact criteria can be found for the selection of appropriate nanomaterials and their properties for a specific application. In most research studies, the nanoparticlesâ material and properties have not been selected based on estimated values so that all the aspects of desired application could be considered simultaneously. The wide spread use of nanomaterials can lead to cost effective solutions as well. Therefore, it seems there should be a sense of techno-economic optimization in exploiting nanomaterials for solar thermal energy storage applications. The optimization should cover the key parameters, particularly nanoparticle type, size, loading and shape which depends on the sort of application and also dispersion technology. Â© 2017, Springer-Verlag GmbH Germany, part of Springer Nature.